Conducting Field Research on Terrorism: a Brief Primer - Adam Dolnik (Perspectives on Terrorism, 2011)
This article focuses on the practical aspects of field research on terrorism. Firstly, it  outlines some issues involved in the process of attaining a human research ethics/institutional review board clearance in order to be able to even begin the field research. It suggests some ways in which researchers can positively influence this review process in their favor. Secondly, the article focuses on the real and perceived dangers of field research, identifying practical steps and preparatory activities that can help researchers manage and reduce the risks involved. The article also covers the formalities and dilemmas involved in gaining access to the field. It then provides some insights into the topic of operating in conflict zones, followed by a section covering the ways of gaining access to sources, effective communication skills and influence techniques and addresses key issues involved in interviewing sources in the field. The final section focuses on identifying biases and interfering factors which researchers need to take into account when interpreting the data acquired through interviews. This article is a modest attempt to fill a gap in the literature on terrorism research by outlining some of the key issues involved in the process of doing field research. It incorporates insights from diverse disciplines as well as the author’s personal experiences of conducting field research on terrorism in places like Afghanistan, Pakistan, Chechnya, Ingushetia, Colombia, Mindanao, Uganda, Indonesia, Democratic Republic of Congo, Sudan, and India.